Adrenaline and vasopressin for cardiac arrest - Finn, Judith; Jacobs, I.; Williams, T.; Gates, S.; Perkins, G. (John Wiley & Sons, Ltd., 2019)
Background: Adrenaline and vasopressin are widely used to treat people with cardiac arrest, but there is uncertainty about the safety, effectiveness and the optimal dose. Objectives: To determine whether adrenaline or vasopressin, or both, administered during cardiac arrest, afford any survival benefit. Search methods: We searched the Cochrane Central Register of Controlled Trials, MEDLINE, Embase and DARE from their inception to 8 May 2018, and the International Liaison Committee on Resuscitation 2015 Advanced Life Support Consensus on Science and Treatment Recommendations. We also searched four trial registers on 5 September 2018 and checked the reference lists of the included studies and review papers to identify potential papers for review. Selection criteria: Any randomised controlled trial comparing: standard-dose adrenaline versus placebo; standard-dose adrenaline versus high-dose adrenaline; and adrenaline versus vasopressin, in any setting, due to any cause of cardiac arrest, in adults and children. There were no language restrictions. Data collection and analysis: Two review authors independently identified trials for review, assessed risks of bias and extracted data, resolving disagreements through re-examination of the trial reports and by discussion. We used risk ratios (RRs) with 95% confidence intervals (CIs) to compare dichotomous outcomes for clinical events. There were no continuous outcomes reported. We examined groups of trials for heterogeneity. We report the quality of evidence for each outcome, using the GRADE approach. Main results: We included 26 studies (21,704 participants). Moderate-quality evidence found that adrenaline increased survival to hospital discharge compared to placebo (RR 1.44, 95% CI 1.11 to 1.86; 2 studies, 8538 participants; an increase from 23 to 32 per 1000, 95% CI 25 to 42). We are uncertain about survival to hospital discharge for high-dose compared to standard-dose adrenaline (RR 1.10, 95% CI 0.75 to 1.62; participants = 6274; studies = 10); an increase from 33 to 36 per 1000, 95% CI 24 to 53); standard-dose adrenaline versus vasopressin (RR 1.25, 95% CI 0.84 to 1.85; 6 studies; 2511 participants; an increase from 72 to 90 per 1000, 95% CI 60 to 133); and standard-dose adrenaline versus vasopressin plus adrenaline (RR 0.76, 95% CI 0.47 to 1.22; 3 studies; 3242 participants; a possible decrease from 24 to 18 per 1000, 95% CI 11 to 29), due to very low-quality evidence. Moderate-quality evidence found that adrenaline compared with placebo increased survival to hospital admission (RR 2.51, 95% CI 1.67 to 3.76; 2 studies, 8489 participants; an increase from 83 to 209 per 1000, 95% CI 139 to 313). We are uncertain about survival to hospital admission when comparing standard-dose with high-dose adrenaline, due to very low-quality evidence. Vasopressin may improve survival to hospital admission when compared with standard-dose adrenaline (RR 1.27, 95% CI 1.04 to 1.54; 3 studies, 1953 participants; low-quality evidence; an increase from 260 to 330 per 1000, 95% CI 270 to 400), and may make little or no difference when compared to standard-dose adrenaline plus vasopressin (RR 0.95, 95% CI 0.83 to 1.08; 3 studies; 3249 participants; low-quality evidence; a decrease from 218 to 207 per 1000 (95% CI 181 to 236). There was no evidence that adrenaline (any dose) or vasopressin improved neurological outcomes. The rate of return of spontaneous circulation (ROSC) was higher for standard-dose adrenaline versus placebo (RR 2.86, 95% CI 2.21 to 3.71; participants = 8663; studies = 3); moderate-quality evidence; an increase from 115 to 329 per 1000, 95% CI 254 to 427). We are uncertain about the effect on ROSC for the comparison of standard-dose versus high-dose adrenaline and standard-does adrenaline compared to vasopressin, due to very low-quality evidence. Standard-dose adrenaline may make little or no difference to ROSC when compared to standard-dose adrenaline plus vasopressin (RR 0.97, 95% CI 0.87 to 1.08; 3 studies, 3249 participants; low-quality evidence; a possible decrease from 299 to 290 per 1000, 95% CI 260 to 323). The source of funding was not stated in 11 of the 26 studies. The study drugs were provided by the manufacturer in four of the 26 studies, but neither drug represents a profitable commercial option. The other 11 studies were funded by organisations such as research foundations and government funding bodies. Authors' conclusions: This review provides moderate-quality evidence that standard-dose adrenaline compared to placebo improves return of spontaneous circulation, survival to hospital admission and survival to hospital discharge, but low-quality evidence that it did not affect survival with a favourable neurological outcome. Very low -quality evidence found that high-dose adrenaline compared to standard-dose adrenaline improved return of spontaneous circulation and survival to admission. Vasopressin compared to standard dose adrenaline improved survival to admission but not return of spontaneous circulation, whilst the combination of adrenaline and vasopressin compared with adrenaline alone had no effect on these outcomes. Neither standard dose adrenaline, high-dose adrenaline,vasopressin nor a combination of adrenaline and vasopressin improved survival with a favourable neurological outcome. Many of these studies were conducted more than 20 years ago. Treatment has changed in recent years, so the findings from older studies may not reflect current practice.